(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
Integral ecological transition and religious discrimination of migrant women in the Mediterranean SOMMARIO: 1. Ecologia integrale e parità di genere - 2. Flussi migratori nel Mediterraneo e discriminazioni religiose femminili - 3. Interventi europei di collaborazione interculturale nel Mare nostrum - 4. Verso un’unica polis euromediterranea? ABSTRACT: In this essay it is hoped that the current development model will be overcome, because it is highly polluting and unfair from a socio-economic point of view, based as it is on competition and prevarication, the result of male hegemony in decision-making bodies and therefore discriminating for weaker and for women. These, on the other hand, must guide an integral ecological transition, because they are more inclined to the custody of creation and future generations, as well as to the improvement of the general living conditions of society, through sharing and dialogue, rather than with imposition and hard confrontation, as Pope Francis claims, in the encyclical Laudato si’. In particular, the ecological and social degradation caused by the androcentric system has increased the flows of migrants so-called environmental, which cross the Mediterranean Sea undergoing abuse and discrimination including religious ones. Above all, Muslim migrant women are more vulnerable also due to the misogynistic cultural heritage resulting from an erroneous and obsolete interpretation of the Koranic texts. Europe can be more involved in the fight against the negative consequences of climate change and discrimination against migrants, implementing policies inspired by sustainable development and intercultural solidarity, also with a view to fostering the ambitious and suggestive attempt to reach a integrated Euro-Mediterranean area.